2022
DOI: 10.31590/ejosat.1047514
|View full text |Cite
|
Sign up to set email alerts
|

Osmaniye İlinde Sahipsiz Köpeklerin Rehabilitasyonu ve Viral Enfeksiyon Profilaksisi

Abstract: değişiklikleri ile ilgili yönetmelikler kapsamında, insan, hayvan ve çevre sağlığını iyileştirmeye yönelik olarak kurumların bilimsel ve teknolojik imkanlarından faydalanarak sahipsiz köpeklerin rehabilitasyonu ve viral enfeksiyon proflaksisinin sağlanmasıdır. 12 aylık çalışma kapsamında, Osmaniye ilinde yaşayan 296 sahipsiz köpekten 259'una rehabilitasyon uygulandı. Hastalık görülen 106 köpekten 77'de (%72,6) viral antijen saptandı ve hematolojik ve serolojik muayeneler yapılarak tedavi uygulandı. Köpeklerden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Pratelli et al (2002 and and Rawland et al ( 2021) reported the ELISA is a sensitive test method for detecting the rising antibody titers against CCoV and is significantly more sensitive than the virus neutralization test and stated that it can be used as an alternative technique to the virus neutralization test. In different studies Avcı et al 24.4% (2015) and 14.87% (2016), Gür et al (2008) 96.5% andTekelioglu et al (2021) 19.8% were reported seropositivity of CCoV in dogs in Türkiye. Furthermore, in molecular and bioinformatics Yesilbag et al (2004) reported 15.5% CCoV positivity by RT-PCR and Aktutay et al (2020) reported CCoV strains from different genogroups are circulating in Türkiye.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Pratelli et al (2002 and and Rawland et al ( 2021) reported the ELISA is a sensitive test method for detecting the rising antibody titers against CCoV and is significantly more sensitive than the virus neutralization test and stated that it can be used as an alternative technique to the virus neutralization test. In different studies Avcı et al 24.4% (2015) and 14.87% (2016), Gür et al (2008) 96.5% andTekelioglu et al (2021) 19.8% were reported seropositivity of CCoV in dogs in Türkiye. Furthermore, in molecular and bioinformatics Yesilbag et al (2004) reported 15.5% CCoV positivity by RT-PCR and Aktutay et al (2020) reported CCoV strains from different genogroups are circulating in Türkiye.…”
Section: Discussionmentioning
confidence: 95%
“…Mortality was observed to be higher in co-infected dogs. Jeoung et al (2008) in Korea, Tekelioglu et al (2021) in Türkiye, were reported coinfections with CCoV and CPV amongst dog population previously (Decaro and Buonavoglia 2011;El Wahed and Truyen 2021;Haake et al, 2020;Jeoung et al, 2008 andTekelioglu et al, 2021;Zapulli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations